2021
DOI: 10.21203/rs.3.rs-415530/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychometric Properties of the Croatian Version of the 25-item National Eye Institute Visual Function Questionnaire (NEI VFQ-25)

Abstract: Purpose: The purpose of study was to translate, adapt and validate the Croatian version of the 25-item National Eye Institute Visual Function Questionnaire (NEI VFQ-25) in participants with visual impairment. This study also aims at evaluating the relationship between visual impairment and health-related quality of life (HRQoL).Methods: The prospective observational study was conducted at the University Hospital Centre Zagreb, Department of Ophthalmology. The sample consisted of 175 patients with four chronic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The results showed that the studied elderly have a good VRQoL level. In some studies, VRQoL has been reported as moderate [12,[33][34][35][36], in some studies similar to the present study as well [20,24,25,37,38] and in some studies as poor [19]. Since VI increase with age and affect the quality and performance of people's vision, and the majority of the elderly studied were in the age group of 60-70 years, so their quality of life was better.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The results showed that the studied elderly have a good VRQoL level. In some studies, VRQoL has been reported as moderate [12,[33][34][35][36], in some studies similar to the present study as well [20,24,25,37,38] and in some studies as poor [19]. Since VI increase with age and affect the quality and performance of people's vision, and the majority of the elderly studied were in the age group of 60-70 years, so their quality of life was better.…”
Section: Discussionsupporting
confidence: 73%
“…Regarding gender, since there is no structural or genetic and biological difference between women and men in eyes, in addition, other factors such as education level and occupation were not signi cantly related to VRQoL, so, there was no signi cant difference between the quality of life of elderly men and women. The results of the previous studies are different, as in some studies quality of life was related to age, gender, occupation and education [12,24,25,29,43,44] and in some studies, these relationships were not signi cant [20,36,45]. Therefore, wider investigations in this eld seem necessary.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies have shown that the VFQ-25 score is a good scale for evaluating the severity of symptoms in patients with vitreous opacities and has reliable reliability and validity [14]. e VFQ-25 scale shows high internal consistency (Cronbach α range 0.739-0.932) and high test-retest reliability (intraclass correlation coefficient 0.876-0.975) [15].…”
Section: Discussionmentioning
confidence: 99%